Refractory iatrogenic pigmentary glaucoma secondary to cosmetic laser treatment: A case report. Issue 2 (March 2023) - Ong, Ariel Yuhan; Ching-A-Sue, Gemma; Krilis, Matthew; Guirao-Navarro, Maria Concepion; Hornby, Stella; Jutley, Gurjeet
Purpose: To report a case of bilateral iatrogenic pigmentary glaucoma secondary to cosmetic iris-lightening laser treatment. Case report: A 39-year-old patient presented with bilateral iatrogenic pigmentary glaucoma. She had elevated intraocular pressures (IOPs), scattered iris pitting, and intense angle pigmentation secondary to the cosmetic laser treatment she underwent 4 weeks prior to presentation. Her IOPs were refractory to maximal medical treatment and she subsequently underwent trabeculectomy. Conclusion: The true scale of complications related to cosmetic laser treatments is as yet unknown. Robust clinical investigations into its safety profile, including long-term data, are required. Prospective patients should consider this with great care. Clinicians should be aware of the potential risks of this procedure, as early recognition of cosmetic laser-induced pigmentary glaucoma may avert further sequelae.